Studi Putusan Muktamar NU Tentang Kawin Gantung Perspektif Peraturan Perlindungan Anak - Mohammad Fauzan Ni'ami (Fakultas Syariah UIN Sultan Maulana Hasanuddin Banten, 2022)
This paper examines the 32nd NU Congress decision on Hanging Marriage, where there are both pros and cons to the decision’s outcome. Some nahdiyyin residents also rejected the decision’s outcomes for a variety of reasons, including the fact that marriages based on this model were no longer relevant to the times. Congress’s decision should not be underestimated because it serves as a reference and guide in the community’s daily practice. The purpose of this paper is to examine the construction of the 32nd NU Congress decision on Hanging Marriage, which is then re-examined using child protection regulations. This paper is a library research paper that employs descriptive analysis techniques. The findings of this study show that the law used in the construction of istinbaṭ is still ilhaqul māsāil bi nażha’iriha, which still dominates texts in classical books. Furthermore, in the context of the review of child protection, the decision of the 32nd NU Congress regarding Hanging Marriage is irrelevant to the current situation and violates children’s rights.